Biological Properties and Absolute Configuration of Flavanones From Calceolariathyrsiflora Graham - Valdés, Ernesto; González, César; Díaz, Katy; Vásquez-Martínez, Yesseny; Mascayano, Carolina; Torrent, Claudia; Cabezas, Francisco; Mejias, Sophia; Montoya, Margarita; Cortez-San Martín, Marcelo; Muñoz, Marcelo A.; Joseph-Nathan, Pedro; et al. (Frontiers in Pharmacology, 2020)
Flavanones (–)-(S)-4'-hydroxy-7-methoxyflavanone (1) and (–)-(S)-3',4'-dihydroxy-7-methoxyflavanone (2) were isolated from the extracts of Calceolaria thyrsiflora, an endemic perennial small shrub growing in the central zone of Chile. The absolute configuration of these compounds was resolved by optical rotation experiments and in silico calculations. Three analogs (3, 4 and 5) were synthesized to do structure-activity relationships with the biological assays studied. Biological tests revealed that only flavanone 2 exhibited a moderate inhibitory activity against the methicillin-resistant strain S. aureus MRSA 97-77 (MIC value of 50 g/mL). In addition, flavanone 2 showed a potent, selective, and competitive inhibition of 5-hLOX in accordance with the anti-inflammatory properties attributed to this plant. Also, 2 exhibited cytotoxic and selective effects against B16-F10 (8.07 µM) but 4.6- and 17-fold lesser activity than etoposide and taxol.